Aplikasi Etika Makan dan Minum Mahasiswi IAIN Imam Bonjol Padang di Kos 2a Kelurahan Anduring Kecamatan Kuranji Kota Padang - Sabiruddin Sabiruddin (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2015)
Ethical eating and drinking is an important thing when going to eat a meal and drink . Prophet Muhammad as a role model for human beings has been delivered through the ordinance traditions he ate and drank the good and the true . What has been delivered through the hadith of the Prophet , he also has no health menduung scientific research . However , the procedure of eating and drinking the right of this hit when its application . Some of them because as eating and drinking the wrong hard weeks to be changed . It so happens to a student who lives in a boarding IAIN 2A